PREVENTION OF WHITE SPOT LESION IN ORTHODONTIC PATIENTS USING CASEIN PHOSPHOPEPTIDE-STABILIZED AMORPHOUS CALCIUM PHOSPHATE -A SYSTEMATIC REVIEW - DEEPA GURUNATHAN; SUJATHA SOMASUNDARAM (International Journal of Pharma and Bio Sciences, 2015)
Early demineralization around orthodontic brackets causes white or brown marks during fixed orthodontic treatment. There is an increased risk of accumulation of dental plaque associated with increased risk of rapid demineralization of the enamel of teeth. However, demineralization is an early, but reversible, stage in the development of tooth. Therefore, remineralising agents were used to treat white lesions in postorthodontic patients. Review question was Prevention of white sot lesions using CPP-ACP. An electronic search was done in Pubmed, Cochrane and Science Direct. One randomized control trial was identified for the review. It is seen that more evidence is required before the application of CPP-ACP to prevent white spot lesions in orthodontic patients.